Confined crystallization of polymers within anodic aluminum oxide templates. Issue 18 (23rd July 2014) - Michell, Rose Mary; Blaszczyk‐Lezak, Iwona; Mijangos, Carmen; Müller, Alejandro J.
ABSTRACT In this article, a review of recent literature on confined crystallization within nanoporous anodic aluminum oxide (AAO) templates is presented. For almost all infiltrated polymeric materials, crystal orientation within the nanopores is a function of pore diameter. Tc and Tm usually decrease and are a function of pore size. When no pore interconnection remains, the crystallization occur at large supercoolings in heterogeneity free environments. Hence, the nucleation mechanism changes from heterogeneous to surface or homogeneous nucleation. The crystallization kinetics of infiltrated polymers should be close to first order, since in confined environments nucleation is the determining step of the overall crystallization and Avrami indexes (n) of ∼1 (or lower in some cases) should be obtained. Examples are provided where these conditions have been met and first order kinetics (n = 1) were measured as opposed to higher orders (n = 3−4) for the same polymer in the bulk. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2014, 52, 1179–1194